2014
DOI: 10.1007/s00464-014-3741-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic versus open component separation: systematic review and meta-analysis

Abstract: This systematic review and meta-analysis comparing MICST to open CST suggests MICST is associated with decreased overall post-operative wound complication rates. Further prospective studies are needed to verify these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 63 publications
(45 reference statements)
0
31
0
5
Order By: Relevance
“…The recurrence rate is (in the available non-controlled studies) reported comparably high (10-35%) and it is higher without mesh reinforcement [57][58][59][60][61][62][63][64][65]. The method can be performed in principal laparoscopically, too [66][67][68] and with advantages in obese patients [69]. Components separation surgical outcomes were similar whether or not the rectus complex was violated [70].…”
Section: Components Separationmentioning
confidence: 96%
“…The recurrence rate is (in the available non-controlled studies) reported comparably high (10-35%) and it is higher without mesh reinforcement [57][58][59][60][61][62][63][64][65]. The method can be performed in principal laparoscopically, too [66][67][68] and with advantages in obese patients [69]. Components separation surgical outcomes were similar whether or not the rectus complex was violated [70].…”
Section: Components Separationmentioning
confidence: 96%
“…19 The literature search also identified 6 systematic reviews, 2 of which had further meta-analyses. 20,21 Three of the systematic reviews compared anterior with endoscopic anterior components separation, a fourth one compared different techniques of components separation (2-part study), the fifth study assessed different surgical methods of giant hernia repair including hernioplasty and components separation, and the sixth paper investigated the quality of life following open hernia repair including satisfaction from component separation technique. [20][21][22][23][24][25] The 3 retrospective studies comparing posterior components separation with other techniques that met the inclusion criteria are Krpata et al, Cobb et al, and Holihan et al 23,26,27 The different characteristics of these are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…While effective, this technique necessitates large subcutaneous flaps and is associated with significant wound complications including infection, intra‐abdominal abscess, enter cutaneous fistula, and ventral hernia formation . Although these complications could be reduced by providing tension in the midline with negative pressure dressing to offset the traction created by the lateral abdominal wall, ventral hernia formation rates were still substantial due to the invasiveness of the technique . The use of minimally invasive CST presented a promising option for decreasing complications; however, it was also associated with high recurrence rates …”
Section: Discussionmentioning
confidence: 99%
“…6,7 Although these complications could be reduced by providing tension in the midline with negative pressure dressing to offset the traction created by the lateral abdominal wall, 8 ventral hernia formation rates were still substantial due to the invasiveness of the technique. 9,10 The use of minimally invasive CST presented a promising option for decreasing complications 11 ; however, it was also associated with high recurrence rates. 12 Botulinum toxin A (BTA) is a neurotoxic protein produced by Clostridium botulinum, which causes reversible (Temporary) muscular paralysis by inhibiting the release of acetylcholine at the neuromuscular junction.…”
Section: Discussionmentioning
confidence: 99%